TOWARDS A TAXONOMY FOR PUBLIC AND COMMON PROPERTY. (March 2019) - Rodgers, Christopher
Abstract: This article argues that public property rights should be recognised as a separate category of property interest, different and distinct from private and common property interests and conferring distinctive rights and obligations on both "owners" and members of the public. It develops a taxonomy to differentiate private, public and common property rights. The article concludes that it is a mistake to think in terms of "private property", "common property" or "public property". The division and allocation of resource entitlements in land can result in private, common and public property rights subsisting over the same land simultaneously, in different combinations and at different times. The categorisation of property interests in land (as private, common or public) may also shift and change from time to time. The article considers the importance of distinguishing between private, common and public property interests for developing new strategies for environmental governance, and for implementing the effective protection of natural resources.